Transformation mechanism of polycyclic aromatic hydrocarbons and hydrogen production during the gasification of coking sludge in supercritical water. (August 2022) - Zhong, Jun; Zhu, Wei; Wang, Chenyu; Mu, Biao; Lin, Naixi; Chen, Sipeng; Li, Zhuo
Abstract: In this study, the characteristic of hydrogen production and polycyclic aromatic hydrocarbons (PAHs) transformation during supercritical water gasification (SCWG) of coking sludge (400 °C - 450 °C, 1 min–30 min) were explored. The total gas yield was between 0.62 mol/kg OM and 1.05 mol/kg OM (on dry basis), and the proportion of CH4 and H2 was only between 5.41% and 6.44%. PAH content were increased from 194.92 mg/kg to 326.04 mg/kg, and mainly high molecular weight PAHs, which were formed from the Diels-Adler reaction of single aromatic hydrocarbon and the addition reaction of low molecular weight PAHs. High reaction temperature favored more active PAH formation than reaction time. The possible control methods for PAH formation during SCWG of coking sludge was proposed. H2 O2 and KOH addition effectively reduce PAHs amount in solid residues by 46.67% and 38.33%, and KOH performed positive effect on hydrogen production. The work revealed that the inhibition of PAHs and hydrogen production were achieved from SCWG of coking sludge with KOH addition. Graphical abstract: Image 1 Highlights: Gasification of coking sludge in supercritical water was tested. PAH concentration increased during gasification process. High temperature and prolonged time favored HMW PAH formation. KOH additive achieves integrated H2 production and PAH inhibition.